Correlation between spin structure oscillations and domain wall velocities - Bisig, André; Stärk, Martin; Mawass, Mohamad-Assaad; Moutafis, Christoforos; Rhensius, Jan; Heidler, Jakoba; Büttner, Felix; Noske, Matthias; Weigand, Markus; Eisebitt, Stefan; Tyliszczak, Tolek; Van Waeyenberge, Bartel; et al. (Nature communications, 2013)
Magnetic sensing and logic devices based on the motion of magnetic domain walls rely on the precise and deterministic control of the position and the velocity of individual magnetic domain walls in curved nanowires. Varying domain wall velocities have been predicted to result from intrinsic effects such as oscillating domain wall spin structure transformations and extrinsic pinning due to imperfections. Here we use direct dynamic imaging of the nanoscale spin structure that allows us for the first time to directly check these predictions. We find a new regime of oscillating domain wall motion even below the Walker breakdown correlated with periodic spin structure changes. We show that the extrinsic pinning from imperfections in the nanowire only affects slow domain walls and we identify the magnetostatic energy, which scales with the domain wall velocity, as the energy reservoir for the domain wall to overcome the local pinning potential landscape. A prerequisite for using domain walls in logic or sensing devices is a thorough knowledge of the properties and precise control. Here the authors monitor the domain wall motion in curved nanowires by stroboscopic imaging and find a regime of oscillating velocity and spin structure below the Walker breakdown.